Ritual da Tucandeira da etnia Sateré-Mawé : língua, memória e tradição cultural - Carvalho, Joelma Monteiro de (2015)
This paper presents an analysis of ethnographic and ethno-linguistic nature that aims to analyze, under the Semiotics of Culture approach, the semiotic representation of the Tucandeira ant, in the context of the Tucandeira Ant Ritual, a rite of passage in the Sateré-Mawé culture, which marks the transition from childhood to adulthood. For this, it describes the ritual, displaying its structure, consisting of verbal and nonverbal signs and it also seeks to understand its socio-cultural function, comparing its performance by the Sateré-Mawé ethnicity living in Indigenous Lands (TI) and in Manaus. Data for the study were collected through open interviews and oral testimonials, together with the Sateré-Mawé people, in the age range of 10-65 years old living in Manaus and in Indigenous Lands (TI) in the regions of the Andirá and Marau rivers, belonging respectively to the municipalities of Barreirinha and Maués. This paper is organized in three stages. The first stage proposes some reflections on ethnographic and ethno-linguistic aspects of the Sateré-Mawé ethnicity, history to the present, emphasizing the socio-cultural and linguistic contexts that characterize and strengthen the culture, memory and ethnic manifestation. In the second stage, the ritual organization is shown in a descriptive way: before, during and afterwards. In the meantime, reflections are made on the process of social change by which the neophyte of the ethnic group passes when attending the ceremony, placing his hands inside the gloves with Tucandeiras at least twenty times, in order to thus complete the cycle started. It also exposes about the evolutions that occurred in this ritual because of cultural hybridization experienced by these communities. In the third stage, this paper describes and analyzes the elements that make up the Tucandeira Ant Ritual, its symbolism and function in the linguistic and socio-cultural context of this ethnic group. The theoretical framework that supported this research are extended to the field of ethno-linguistic and semiotic representation, based on the studies of Guinsburg (1988), Turner (2005), Rodrigues (2009), Lima Barreto (2010), and Pietroforte (2012). As a result of analysis of the survey data, it is pointed out, among others, that among the elements that compose the ritual, the Tucandeira ant is the main figure. Its name means "the one that hurts a lot", and several meanings in the cultural context are added to it. It represents the woman who attracts and delights men, motivating them to participate in this ceremony. The Tucandeira also acts as an indigenous vaccine, which prevents diseases and strengthens Sateré men’s bodies. Thus, under the semiotic approaches, in particular the Semiotics of Culture, according to Pais (2009), the aim is to analyze and comprehend the semiotic value of that element in the enunciative context of the Sateré-Mawé male initiation ritual. Keywords: Ethnolinguistics; Sateré-Mawé; Tucandeira; Ritual.